BAFullInstructions0

# All variables are enter only variables you can access

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: e in memory 5: 1. Press or 2. Press 95 until M5 is displayed. . Example: Multiplying a Value in a Memory To multiply the value in memory 0 by 95. 1. Press or 2. Press < 95 until M0 is displayed. . Example: Dividing a Value in a Memory To divide the value in memory 6 by 95. 1. Press or 2. Press 95 until M6 is displayed. . Example: Raising a Value in Memory to a Power To raise the value in memory 7 to the 66th power. 1. Press or 2. Press 66 until M7 is displayed. . Chapter 7: Using Other Worksheets 69 70 Chapter 7: Using Other Worksheets APPENDIX A Reference Information This appendix provides supplemental information on formulas, error conditions, and accuracy that may be helpful as you use your calculator. Formulas Formulas used internally by your calculator are included here for your information. Time Value of Money i = [e ( y × ln( x + 1))] − 1 where: PMT y x C/Y P/Y I/Y 0 = C/Y P P/Y = (.01 I/Y) P C/Y = compounding periods per year = payment periods per year = interest rate per year i = (− FV ÷ PV )(1 ÷ N ) − 1 where: PMT = 0 The iteration used to compute i: 1 − (1 + i) 0 = PV + PMT × Gi i I/Y = 100 C/Y −N −N + FV × (1 + i) [ e(y × ln( x + 1)) − 1] where: x = i y = P/Y P C/Y Gi = 1 + i × k where: k = 0 for end-of-period payments k = 1 for beginning-of-period payments Appendix A: Reference Information 71 Time Value of Money (Continued) PMT × Gi − FV × i ln PMT × Gi + PV × i N= ln(1 + i) where: i N= − ( PV 0 + FV ) ÷ PMT where: i = 0 PMT = −i PV + FV × PV + Gi (1 + i ) N − 1 where: i 0 PMT = −( PV + FV ) ÷ N where: i = 0 PMT × Gi 1 PMT × Gi PV = − FV × − N i i (1 + i) where: i 0 PV = −( FV + PMT × N ) where: i = 0 FV = PMT × Gi PMT × Gi − ( 1 + i )N × PV + i i where: i FV = − ( PV 0 + PMT × N ) where: i = 0 72 Appendix A: Reference Information Amortization If computing bal( ), pmt2 = npmt Let bal(0) = RND(PV) Iterate from m = 1 to pmt2 [ Im = RND RND12( −i × bal( m − 1)) bal( m) = bal( m − 1) − Im + RND( PMT ) then: bal ( ) = bal ( p...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online